Democratizing tech giants! A roadmap - Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
How society should deal with the self-strengthening Tech Giants is a muchdiscussed issue. We suggest to democratize them by giving users a say in their decisions. With newly-developed collective decision rules and user councils, democratization of Tech Giants becomes feasible.
Keywords: 330